2021
DOI: 10.21660/2021.82.j2114
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Investigation on Jaboi Manifestation, Jaboi Volcano, Sabang, Indonesia

Abstract: Geochemical studies have been conducted in the geothermal system of Jaboi manifestation, Sabang, Aceh. There are three sub-area of geothermal water sites in this area, that are production-injection wells of PT Sabang Geothermal Energy, Jaboi crater, and hot spring pond. The fumaroles were also found in the Jaboi crater. The mineral contents were analyzed by ion chromatography, alkalimetry, and spectrophotometry, the isotope was determined by Laser Absorption Spectrophotometer, while the gas contents were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Several areas in Aceh Province have geothermal potential stemming from volcanic activities, including Mount Seulawah Agam, located in the Aceh Besar District [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several areas in Aceh Province have geothermal potential stemming from volcanic activities, including Mount Seulawah Agam, located in the Aceh Besar District [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…According to research conducted by Idroes et al [26], there are three sub-areas of geothermal heat sources in the Jaboi area, as shown in Figure 4. These include the production injection wells of PT.…”
Section: Results Of the Aras Methods On The Jaboi Sabang Geothermal P...mentioning
confidence: 99%
“…The criteria used in this test align with those in the Seulawah study. Idroes et al [27] identified three subareas in the Jaboi region: production-injection wells (SP1_Jaboi and SP2_Jaboi), hot water pond (KP_Jaboi), and Jaboi crater (JK1_Jaboi, JK2_Jaboi, and JK4_Jaboi).…”
Section: The Results Of the Moora Methods On Jaboi Sabang Geothermal ...mentioning
confidence: 99%